Keragaan Komunikasi Pada Gapoktan Penerima Dana Program Pengembangan Usaha Agribisnis Perdesaan Di Kecamatan Siak Kecil Kabupaten Bengkalis Riau - Susy Hartati; Amiruddin Saleh; Basita Sugihen (Jurnal Komunikasi Pembangunan, 2011)
ABSTRACT Rural Agribusiness Development Program (PUAP) is a program that focuses in reducing poverty and also creating a huge work field in rural area by providing venture capital to support on farm and off farm activities. Farmers’ association group (gapoktan) as an implementer of PUAP has a pivotal function to distribute incentives, venture capital, and also as the managers of all the programs given. From that perspective gapoktan holds an important role for the success of this program. Communication process among group members in gapoktan and interpersonal communication between agents of change and the gapoktan needed to be inquired because it was estimated as one of the important factor that influencing PUAP program. The objectives of this research were: (1) to describe the characteristic and the communication process (2) to see the communication among agents of change (3) to see the role and the ability of gapoktan (4) to analysis the correlation between all of the variables. This research resulted several outputs, namely: The characteristics were categorized good, role and the ability were not enough, communication of gapoktan was good and the communication agents of change were not enough until less than not enough. There were a significant correlation between the characteristics with the communication of gapoktan, between the communication of agents of change with the role of gapoktan and between role with ability of farmers’ group association. Keywords: communication, farmers’ group association, agent of change, role, ability